2018
DOI: 10.1177/1528083718760802
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of 3D woven preform for improved mechanical performance

Abstract: For structural design applications, through-thickness characteristics of reinforcement played a vital role, which is why 3D woven preforms are recommended for such applications. These characteristics are mainly dependent on the fiber and yarn positioning in reinforcement. Although research has been conducted for characterizing woven composites, special attention has not been made on weave pattern parameter which directly affects the mechanical performance of composites. In this research work, 3D orthogonal lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…They noted that the binding point density between layers improves the out-of-plane properties at the expense of the in-plane properties. From jute yarns, Kashif et al [20] made about 10 3D warp interlock preforms and have concluded, via an ANOVA, that the weave pattern has an impact on mechanical properties of the dry fabric. To improve the mechanical properties of 3D warp interlock composites based on natural fibers, it is essential to control the parameters of the reinforcement architecture, but also to follow the properties at each scale [21,22], because the mechanical properties of plant fibers are often considered to show high variability [23].…”
Section: Introductionmentioning
confidence: 99%
“…They noted that the binding point density between layers improves the out-of-plane properties at the expense of the in-plane properties. From jute yarns, Kashif et al [20] made about 10 3D warp interlock preforms and have concluded, via an ANOVA, that the weave pattern has an impact on mechanical properties of the dry fabric. To improve the mechanical properties of 3D warp interlock composites based on natural fibers, it is essential to control the parameters of the reinforcement architecture, but also to follow the properties at each scale [21,22], because the mechanical properties of plant fibers are often considered to show high variability [23].…”
Section: Introductionmentioning
confidence: 99%
“…The detailed study included with all necessary characterization of dry prefroms may be referred to previous work. 15 Comparison of the tensile strength of prefroms and composites in the warp (A) and weft (B) direction is shown in Figure 3. The readers will find the necessary characterization of dry preforms in previous work.…”
Section: Resultsmentioning
confidence: 99%
“…14 The reader can find the mechanical characterization of preforms and composites in our previous works. 15,16 This study focusses only on the shear beam strength of composites.…”
Section: Introductionmentioning
confidence: 99%
“…However, more test results and research studies are needed in the literature to clarify their influences on their mechanical properties. Accordingly, many research studies have been focused on this problem since the last decade [11–17]. In addition, complex deformations like impact, knife penetration, permeability and formability properties were examined under different structural parameters in other studies [18–21].…”
Section: Introductionmentioning
confidence: 99%